Hierarchies of knowledge about intersectionality in marketing theory and practice. (June 2022) - Rosa-Salas, Marcel; Sobande, Francesca
There is scant research regarding intersectionality and epistemic hierarchies in marketing, including connections and disconnections between knowledge about intersectionality produced in marketing scholarship and practice. Thus, we examine how market logics propelled by gendered racial capitalism and the commercialization of identity politics impact the production of knowledge about intersectionality in the marketing discipline and industry. We consider how the notion of "intersectionality" has been conceptualized and obfuscated in marketing scholarship and entwined industry discourse. Consequently, we provide a genealogy of how "intersectionality" has been framed in marketing studies and industry approaches which reflect the entanglements of knowledge production, the politics of representation, and the marketization of social justice. Overall, we contribute to scholarly interventions regarding how intersecting oppressions influence marketing and critical analyses of it, as well as the complex interrelationship between marketing, commercial representation, and discourses of identity, inequality, and structural change.